Composition for thermally conductive material, thermally conductive material, and method for producing thermally conductive material

A composition of acrylic polymer, polyfunctional monomer, and thermally conductive fillers with specific ratios and sizes enhances thermal conductivity to 7.2 W/m·K, addressing the limitations of conventional materials by maintaining material integrity and surface smoothness.

JP7610264B2Active Publication Date: 2025-01-08KITAGAWA INDS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021184829
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-12
Publication Date
2025-01-08
Estimated Expiration
2041-11-12

AI Technical Summary

Technical Problem

Conventional thermally conductive materials exhibit thermal conductivity of about 3 W/m·K, leaving room for improvement.

Method used

A composition comprising an acrylic polymer, polyfunctional monomer, polymerization initiator, and thermally conductive fillers with specific particle sizes and ratios, including large, medium, and small particle sizes of aluminum nitride and silicon carbide, is used to enhance thermal conductivity to 7.2 W/m·K or more.

Benefits of technology

The composition achieves high thermal conductivity, maintains material shape and hardness, and ensures smooth surface finish with minimal filler adherence during film peeling, facilitating effective heat dissipation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610264000002
    Figure 0007610264000002
  • Figure 0007610264000003
    Figure 0007610264000003
  • Figure 0007610264000004
    Figure 0007610264000004
Patent Text Reader

Abstract

To provide thermally conductive material etc. having high thermal conductivity.SOLUTION: A composition for thermally conductive material has: an acrylic composition including an acrylic polymer obtained by polymerizing one or two or more (meth)acrylate, and including one or two or more (meth)acrylate, a polyfunctional monomer; a polymerization initiator; and a thermally conductive filler, wherein with respect to 100 pts.mass of the acrylic composition, a blending amount of the polyfunctional monomer is 0.1 pts.mass or more and 0.5 pts.mass or less, a blending amount of the polymerization initiator is 0.1 pts.mass or more and 1.5 pts.mass or less, and a blending amount of the thermally conductive filler is 1,550 pts.mass or more and 1,600 pts.mass or less, the thermally conductive filler includes a large particle diameter thermally conductive filler which has a particle diameter of 50 μm or more and 150 μm or less and is composed of an aluminum nitride, a middle particle diameter thermally conductive filler having a particle diameter of 7.5 μm or more and 20 μm or less, and a small particle diameter thermally conductive filler having a particle diameter of 3 μm or less, and with respect to 100 pts.mass of the acrylic composition, a blending amount of the large particle diameter thermally conductive filler is 680 pts.mass or more and 750 pts.mass or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for a thermally conductive material, a thermally conductive material, and a method for producing a thermally conductive material. [Background technology]

[0002] Thermally conductive materials made of acrylic resin filled with thermally conductive filler are known (for example, Patent Document 1). This type of thermally conductive material is used by being placed in contact with a heat generating body such as an electronic component in order to promote heat dissipation from the heat generating body. Specifically, a sheet-shaped thermally conductive material is used by being interposed between a heat generating body (for example, a CPU) and a heat sink. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 4009224 Summary of the Invention [Problem to be solved by the invention]

[0004] The thermal conductivity of conventional thermally conductive materials is approximately 3 W / m·K (for example, Patent Document 1), leaving room for improvement.

[0005] An object of the present invention is to provide a thermally conductive material having high thermal conductivity. [Means for solving the problem]

[0006] The means for solving the above problems are as follows. <1> A composition for a thermally conductive material comprising an acrylic polymer obtained by polymerizing one or more (meth)acrylates, an acrylic composition containing one or more (meth)acrylates, a polyfunctional monomer, a polymerization initiator, and a thermally conductive filler, the content of the polyfunctional monomer being 0.1 parts by mass or more and 0.5 parts by mass or less, the content of the polymerization initiator being 0.1 parts by mass or more and 1.5 parts by mass or less, and the content of the thermally conductive filler being 0.01 parts by mass or more and 0.02 ... a thermally conductive filler having a particle size of 50 μm or more and 150 μm or less and made of aluminum nitride, a medium-sized thermally conductive filler having a particle size of 7.5 μm or more and 20 μm or less, and a small-sized thermally conductive filler having a particle size of 3 μm or less, and the amount of the large-sized thermally conductive filler is 680 parts by mass or more and 750 parts by mass or less per 100 parts by mass of the acrylic composition.

[0007] <2> The blending amount of the medium-sized heat conductive filler is 300 parts by mass or more per 100 parts by mass of the acrylic composition. <1> The thermal conductive material composition according to claim 1 .

[0008] <3> The amount of the small particle diameter thermally conductive filler blended per 100 parts by mass of the acrylic composition is greater than the amount of the medium particle diameter thermally conductive filler blended per 100 parts by mass of the acrylic composition. <1> or <2> The thermal conductive material composition according to claim 1 .

[0009] <4> The above <1> ~ <3> A thermal conductive material comprising a cured product of the composition for a thermal conductive material according to any one of the above items 1 to 5, and having a thermal conductivity of 7.2 W / m·K or more.

[0010] <5> The above <1> ~ <3> 2. A method for producing a thermally conductive material by using the composition for a thermally conductive material described in any one of claims 1 to 11, comprising the steps of: applying the composition for a thermally conductive material to a surface of a first release film to form an object made of the composition for a thermally conductive material; covering the surface of the object with a second release film so that the object is sandwiched between the first release film and the second release film; and hot pressing the object sandwiched between the first release film and the second release film to harden the object, thereby obtaining a highly thermally conductive material made of a hardened object of the object. Effect of the Invention

[0011] According to the present invention, it is possible to provide a thermally conductive material having high thermal conductivity. [Brief description of the drawings]

[0012] [Figure 1] A schematic diagram showing the cross-sectional structure of a thermally conductive material. [Diagram 2] An explanatory diagram showing an example of the use of thermal conductive materials [Diagram 3] A diagram (photo) showing a case where a very small amount of separated material was found to adhere to the release film when it was peeled off from the thermal conductive material. [Figure 4] A diagram (photo) showing a case where separated material is found adhering to the release film when the release film is peeled off from the thermal conductive material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [Heat Conductive Material Composition] The composition for a thermally conductive material of the present invention is a composition for producing a thermally conductive material having high thermal conductivity, and is usually in a liquid state at room temperature (23° C.).

[0014] The thermally conductive material composition mainly contains an acrylic composition, a polyfunctional monomer, a polymerization initiator, and a thermally conductive filler.

[0015] The acrylic composition is a composition containing at least an acrylic polymer obtained by polymerizing one or more (meth)acrylates, and one or more (meth)acrylates. In this specification, "(meth)acrylate" means methacrylate and / or acrylate.

[0016] The acrylic polymer is formed by polymerizing a single or a combination of two or more (meth)acrylates having a linear or branched alkyl group having 2 to 18 carbon atoms (hereinafter, sometimes referred to as "alkyl (meth)acrylates"). Examples of alkyl (meth)acrylates include ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, n-pentyl (meth)acrylate, i-pentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-hexyl (meth)acrylate, octyl (meth)acrylate, i-octyl (meth)acrylate, nonyl (meth)acrylate, i-nonyl (meth)acrylate, i-decyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, i-myristyl (meth)acrylate, stearyl (meth)acrylate, and i-stearyl (meth)acrylate.

[0017] The acrylic composition contains a (meth)acrylate monomer together with an acrylic polymer. The (meth)acrylate monomer may be a single (meth)acrylate (i.e., an alkyl (meth)acrylate) exemplified as the material for the acrylic polymer, or a combination of two or more kinds of the (meth)acrylate, or a (meth)acrylate other than an alkyl (meth)acrylate.

[0018] The acrylic composition may contain other copolymerizable monomers in addition to the acrylic polymer and the (meth)acrylate as a monomer. Examples of the other copolymerizable monomers include copolymerizable vinyl monomers having a vinyl group (e.g., acrylamide, acrylonitrile, methyl vinyl ether, ethyl vinyl ether, vinyl acetate, vinyl chloride, etc.), aromatic monomers (e.g., benzyl (meth)acrylate, phenoxyethyl (meth)acrylate), etc. These may be used alone or in combination of two or more.

[0019] The acrylic composition may further contain aromatic esters.

[0020] As the acrylic composition, commercially available products (for example, Acrylicure (registered trademark) HD-A series manufactured by Nippon Shokubai Co., Ltd.) may be used.

[0021] (Polyfunctional Monomer) A polyfunctional monomer is a monomer having two or more (meth)acryloyl groups in the molecule. In this specification, the term "(meth)acryloyl group" refers to an acryloyl group and / or a methacryloyl group.

[0022] Examples of bifunctional (meth)acrylate monomers having two (meth)acryloyl groups in the molecule include 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, and 2-ethyl-2-butyl-propanediol. (meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol diacrylate, polypropylene glycol di(meth)acrylate, 2,2-bis[4-(meth)acryloxydiethoxyphenyl]propane, 2,2-bis[4-(meth)acryloxypropoxyphenyl]propane, 2,2-bis[4-(meth)acryloxytetraethoxyphenyl]propane, and the like.

[0023] Examples of trifunctional (meth)acrylate monomers include trimethylolpropane tri(meth)acrylate, tris[(meth)acryloxyethyl]isocyanurate, etc. Examples of tetrafunctional or higher (meth)acrylate monomers include dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc.

[0024] The polyfunctional monomers may be used alone or in combination of two or more kinds. Among these polyfunctional monomers, 1,6-hexanediol di(meth)acrylate and the like are preferred.

[0025] The amount of the polyfunctional monomer is 0.1 parts by mass or more, preferably 0.15 parts by mass or more and 0.5 parts by mass or less, preferably 0.4 parts by mass or less, and more preferably 0.3 parts by mass or less, relative to 100 parts by mass of the acrylic composition. When the amount of the polyfunctional monomer is within the above range in the thermal conductive material composition, a thermal conductive material (molded body) having high thermal conductivity and the like can be obtained, and the hardness of the molded body (thermal conductive material) is not too high, and the shape can be maintained.

[0026] (Polymerization initiator) The polymerization initiator is made of a peroxide, and generates radicals when heated to a predetermined temperature or higher. The polymerization initiator is, for example, an organic peroxide such as di-(4-t-butylcyclohexyl) peroxydicarbonate, lauroyl peroxide, t-amylperoxy-2-ethylhexanoate, benzoyl peroxide, t-butylperoxy-2-ethylhexanoate, or 4-(1,1-dimethylethyl)cyclohexanol. Among the polymerization initiators, di-(4-t-butylcyclohexyl) peroxydicarbonate is preferred. These polymerization initiators may be used alone or in combination of two or more.

[0027] The amount of the polymerization initiator is 0.1 parts by mass or more, preferably 0.4 parts by mass or more and 1.5 parts by mass or less, preferably 1.3 parts by mass or less, based on 100 parts by mass of the acrylic composition. When the amount of the polymerization initiator in the thermal conduction composition is within the above range, a thermal conduction material (molded body) having high thermal conductivity and the like can be obtained, and the molded body (thermal conduction material) does not become too hard, so that the shape can be maintained.

[0028] The thermally conductive filler includes a large particle size thermally conductive filler, a medium particle size thermally conductive filler, and a small particle size thermally conductive filler.

[0029] The large-particle-size thermally conductive filler is a thermally conductive filler having a particle size larger than that of the medium-particle-size thermally conductive filler and the small-particle-size thermally conductive filler. The particle size of the large-particle-size thermally conductive filler is 50 μm or more, preferably 55 μm or more, more preferably 60 μm or more, and is 150 μm or less, preferably 130 μm or less, more preferably 110 μm or less.

[0030] The large particle size thermally conductive filler is made of aluminum nitride (AlN) powder (particulate aluminum nitride).

[0031] The medium-sized thermally conductive filler is a thermally conductive filler having a particle size smaller than that of the large-sized thermally conductive filler and a particle size larger than that of the small-sized thermally conductive filler. The particle size of the medium-sized thermally conductive filler is 7.5 μm or more, preferably 8.5 μm or more, more preferably 9.0 μm or more, and 20 μm or less, preferably 16 μm or less, more preferably 13 μm or less.

[0032] The medium-sized thermally conductive filler may be, for example, a powder of silicon carbide (SiC) or the like.

[0033] The small-particle-size thermally conductive filler is a thermally conductive filler having a smaller particle size than the large-particle-size thermally conductive filler and the medium-particle-size thermally conductive filler. The particle size of the small-particle-size thermally conductive filler is 3 μm or less, preferably 2 μm or less, and more preferably 1.5 μm or less. The lower limit of the particle size of the small-particle-size thermally conductive filler is not particularly limited as long as it does not impair the object of the present invention, but is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 0.5 μm or more.

[0034] The small particle diameter thermally conductive filler may be, for example, aluminum oxide (Al2O3) powder.

[0035] The blending amount of the thermally conductive fillers (large particle size thermally conductive fillers, medium particle size thermally conductive fillers, and small particle size thermally conductive fillers) is 1550 parts by mass or more and 1600 parts by mass or less relative to 100 parts by mass of the acrylic composition. When the blending amount of the thermally conductive fillers (large particle size thermally conductive fillers, medium particle size thermally conductive fillers, and small particle size thermally conductive fillers) in the thermally conductive material composition is within the above range, a thermally conductive material (molded body) having high thermal conductivity and the like can be obtained, and the viscosity of the thermally conductive composition and the hardness of the molded body (thermal conductive material) can be prevented from becoming too high.

[0036] The amount of the large-particle-sized thermally conductive filler is 680 parts by mass or more and 750 parts by mass or less relative to 100 parts by mass of the acrylic composition. When the amount of the large-particle-sized thermally conductive filler in the composition for thermally conductive material is within the above range, a thermally conductive material (molded product) having high thermal conductivity and the like can be obtained, the spacing between the large-particle-sized thermally conductive fillers formed in the thermally conductive material is appropriately maintained, and cracks and irregularities are suppressed from being formed on the surface of the thermally conductive material (molded product).

[0037] The amount of the medium-sized thermally conductive filler is preferably 300 parts by mass or more, more preferably 350 parts by mass or more, relative to 100 parts by mass of the acrylic composition. The upper limit of the amount of the medium-sized thermally conductive filler is not particularly limited as long as it does not impair the object of the present invention, but is preferably 450 parts by mass or less, more preferably 400 parts by mass or less, relative to 100 parts by mass of the acrylic composition. When the amount of the medium-sized thermally conductive filler is within the above range, it is easy to obtain a thermally conductive material (molded body) having high thermal conductivity, and it is easy to suppress the viscosity of the thermally conductive composition and the hardness of the molded body (thermal conductive material) from becoming too high. The medium-sized thermally conductive filler is arranged so as to fill the gaps (intervals) formed between the large-sized thermally conductive fillers in the thermally conductive material.

[0038] In the thermally conductive material composition, the amount of the small-particle-size thermally conductive filler blended per 100 parts by mass of the acrylic composition is preferably greater than the amount of the medium-particle-size thermally conductive filler blended per 100 parts by mass of the acrylic composition.

[0039] The amount of the small-particle-sized thermally conductive filler is not particularly limited as long as it does not impair the object of the present invention, but may be, for example, preferably 400 parts by mass or more, more preferably 450 parts by mass or more, preferably 550 parts by mass or less, and more preferably 500 parts by mass or less, relative to 100 parts by mass of the acrylic composition. When the amount of the small-particle-sized thermally conductive filler is within the above range, a thermally conductive material (molded body) having high thermal conductivity and the like can be easily obtained, and the viscosity of the thermally conductive composition and the hardness of the molded body (thermal conductive material) can be easily prevented from becoming too high. In addition, the small-particle-sized thermally conductive filler is arranged in the thermally conductive material so as to fill the gaps (spacing) formed between the large-particle-sized thermally conductive fillers, the gaps formed between the medium-particle-sized thermally conductive fillers, and the gaps (spacing) formed between the large-particle-sized thermally conductive fillers and the medium-particle-sized thermally conductive fillers.

[0040] In this specification, the particle size (μm) of various fillers such as the thermally conductive filler (large particle size thermally conductive filler, medium particle size thermally conductive filler, small particle size thermally conductive filler) is the particle size (D50) based on volume measured by the laser diffraction method. The particle size (D50) can be measured using a laser diffraction type particle size distribution measuring device.

[0041] The thermal conductive material composition may further contain an antioxidant, a plasticizer, and a dispersant.

[0042] (Antioxidants) Examples of the antioxidant include phenol-based antioxidants, phosphorus-based processing heat stabilizers, lactone-based processing heat stabilizers, sulfur-based heat stabilizers, and phenol-phosphorus-based antioxidants. Phenol-based antioxidants are preferred, and hindered phenol-based antioxidants are particularly preferred. The amount of the antioxidant is not particularly limited as long as it does not impair the object of the present invention, and may be, for example, in the range of 2 parts by mass or less (0 to 2 parts by mass) relative to 100 parts by mass of the acrylic composition. The antioxidant is not an essential component in the composition for thermal conductive material, so it may not be included. The antioxidant may be used appropriately for the purpose of long-term stability of the thermal conductive material obtained from the composition for thermal conductive material, hardness adjustment of the thermal conductive material (adjustment of the polymerization reaction of the acrylic resin during production), etc.

[0043] As a commercially available antioxidant, for example, the product name "ADEKA STAB (registered trademark) AO-60" (manufactured by ADEKA Corporation) can be used.

[0044] As the plasticizer, for example, trimellitic acid ester-based plasticizers are preferable. As the trimellitic acid ester-based plasticizers, for example, trioctyl trimellitate, triisononyl trimellitate, triisodecyl trimellitate, 2-ethylhexyl trimellitate, etc. can be mentioned. These may be used alone or in combination of two or more. As a commercially available trimellitic acid ester-based plasticizer, the trade name "ADEKA Cizer (registered trademark) C-880" (manufactured by ADEKA Corporation) can be used.

[0045] The blending amount of the plasticizer is preferably 4 parts by mass or more, more preferably 6 parts by mass or more, preferably 15 parts by mass or less, and more preferably 10 parts by mass or less, relative to 100 parts by mass of the acrylic composition. When the blending amount of the plasticizer is within such a range, it is easy to adjust the thermal conductive material to a desired hardness (Asker C hardness). When the blending amount of the plasticizer is within the above range, it is easy to obtain a thermal conductive material (molded body) having high thermal conductivity, etc., and it is easy to prevent the viscosity of the thermal conductive composition and the hardness of the molded body (thermal conductive material) from becoming too high.

[0046] As the dispersant, for example, polyester phosphate is preferable.

[0047] The amount of the dispersant is preferably 5 parts by mass or more, more preferably 7 parts by mass or more, and preferably 14 parts by mass or less, and more preferably 9 parts by mass or less, relative to 100 parts by mass of the acrylic composition. When the amount of the dispersant is within such a range, crosslinking inhibition is unlikely to occur, making it easy to adjust the viscosity of the composition for thermal conductive materials to an appropriate range, and, for example, when producing a thermal conductive material, it becomes easy to form an application made of the composition for thermal conductive materials on a release film (i.e., it becomes easy to obtain a molded product (e.g., a sheet) of a predetermined shape).

[0048] The thermal conductive material composition may further contain other components as long as the purpose of the present invention is not impaired. Examples of other components include colorants (pigments, dyes, etc.), ultraviolet absorbers, flame retardants, preservatives, solvents, mildew inhibitors, antioxidants, antistatic agents, and tackifiers.

[0049] [Method of manufacturing thermally conductive material] The method for producing a thermally conductive material of the present invention is a method for producing a thermally conductive material by using the above-mentioned composition for a thermally conductive material. The method for producing a thermally conductive material includes an applying step, a coating step, and a heating and pressurizing step.

[0050] The applying step is a step of applying the thermally conductive material composition to the surface of the first release film to form an applied object made of the thermally conductive material composition.

[0051] The covering step is a step of covering the surface of the object with a second release film so that the object is sandwiched between the first release film and the second release film.

[0052] The heating and pressing step is a step of hot pressing the applied material sandwiched between the first release film and the second release film to harden the applied material, thereby obtaining a highly thermally conductive material made of the hardened applied material. The hot pressing conditions may be, for example, a heating temperature of 100°C to 110°C, a pressing time of 5 minutes to 10 minutes, and a pressure of 20 MPa to 40 MPa.

[0053] [Thermal Conductive Material] The thermal conductive material is manufactured using the thermal conductive material composition and has excellent thermal conductivity. Specifically, the thermal conductive material has a thermal conductivity of 7.2 W / m·K or more (preferably 7.5 W / m·K or more, more preferably 8.0 W / m·K or more). The method for measuring the thermal conductivity will be described later. In addition, the thermal conductive material has excellent peelability, as described later. That is, when the release film is peeled off from the surface of the thermal conductive material, a part of the thermal conductive material (separated material) is prevented from adhering to the release film and moving, so that the formation of unevenness on the surface of the thermal conductive material is prevented (that is, the smoothness of the surface of the thermal conductive material is maintained). Therefore, air (air bubbles) is prevented from accumulating between the thermal conductive material and the object to which it is attached, and the high thermal conductivity of the thermal conductive material is maintained. In addition, the thermal conductive material has adhesiveness on its surface. Therefore, the thermal conductive material can be attached to the object by utilizing the adhesiveness (adhesive force) of the surface, and can be positioned relative to the object or fixed to the object.

[0054] The hardness of the thermally conductive material is not particularly limited as long as it does not impair the object of the present invention, and may be appropriately set. The hardness (Asker C hardness) of the thermally conductive material may be, for example, 10 or more and 75 or less.

[0055] FIG. 1 is an explanatory diagram showing a schematic cross-sectional structure of a thermally conductive material 1. The thermally conductive material 1 is a sheet having a predetermined thickness, and includes an acrylic resin layer 2 and a thermally conductive filler 3 contained in the acrylic resin layer 2. The thermally conductive filler 3 is composed of large particle size thermally conductive filler 31, medium particle size thermally conductive filler 32, and small particle size thermally conductive filler 33. Release films 4 and 5 are attached to the front and back surfaces of the thermally conductive material 11, respectively. Release film 5 corresponds to the "first release film," and release film 4 corresponds to the "second release film."

[0056] The release films 4 and 5 are made of PET films having a predetermined thickness. A release agent made of silicone resin or the like may be applied to the portions of the release films 4 and 5 that directly contact the thermally conductive material 11. As the release films 4 and 5, films made of other resins (polyolefin resins or the like) other than PET films may also be used.

[0057] FIG. 2 is an explanatory diagram showing an example of use of the thermally conductive material 1. The thermally conductive material 1 is used, for example, when attaching a heat dissipation member 20 to an electronic component (CPU) 10 mounted on a printed circuit board 11. Specifically, a sheet-shaped heat dissipation member 1 from which release films 4, 5 (see FIG. 1) have been peeled off is attached to the upper surface of the electronic component 10, and then a plate-shaped bottom portion 21 of the heat dissipation member 20 is attached to the heat dissipation member 1. A plurality of heat dissipation fins 22 are provided upright on the bottom portion 21. The heat dissipation member 1 is made of a metal material (e.g., aluminum) having excellent thermal conductivity. Heat generated from the electronic component 10 moves to the heat dissipation member 1 while passing through a conductive path made of heat conductive fillers 3 (31, 32, 33) present in the heat dissipation member 1. Then, the heat is dissipated by the heat dissipation member 1.

[0058] The above-mentioned use example of the thermally conductive material 1 is just an example, and the thermally conductive material 1 may be used for other purposes. EXAMPLES

[0059] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples in any way.

[0060] [Heat Conductive Material Composition] Example 1 A polyfunctional monomer, a polymerization initiator, an antioxidant, a plasticizer, a dispersant, and thermally conductive fillers (large particle size thermally conductive filler, medium particle size thermally conductive filler, and small particle size thermally conductive filler) were added to 100 parts by mass of the acrylic composition in the amounts (parts by mass) shown in Table 1, and mixed to obtain a composition for thermally conductive materials of Example 1. Details of each component are as follows.

[0061] "Acrylic composition": Trade name "Acrycure (registered trademark) HD-A218" (manufactured by Nippon Shokubai Co., Ltd., a composition containing a (meth)acrylic acid ester polymer (an example of an acrylic polymer), 2-ethylhexyl acrylate (an example of a (meth)acrylate), and aromatic esters)

[0062] "Multifunctional monomer": Product name "Light Acrylate (registered trademark) 1.6HX-A" (manufactured by Kyoeisha Chemical Co., Ltd., 1,6-hexanediol diacrylate)

[0063] "Polymerization initiator": Trade name "Perkadox (registered trademark) 16" (manufactured by Kayaku Akzo Co., Ltd., di-(4-tert-butylcyclohexyl) peroxydicarbonate, 4-(1,1-dimethylethyl)cyclohexanol)

[0064] "Plasticizer": Product name "ADEKA Cizer (registered trademark) C-880" (ADEKA Corporation, trimellitic acid ester plasticizer, viscosity: 100 mPa·s (25°C))

[0065] "Dispersant": Product name "BYK-W 9010" (BYK Co., Ltd., phosphate polyester)

[0066] "Antioxidant": Trade name "ADEKA STAB (registered trademark) AO-60" (manufactured by ADEKA Corporation, tetrakis[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane)

[0067] "Aluminum nitride (large particle size thermal conductive filler)": Product name "HF-100" (manufactured by Combustion Synthesis Co., Ltd., particle size 100 μm)

[0068] "Silicon carbide (large particle size thermal conductive filler)": Product name "NGF180" (manufactured by Pacific Random Co., Ltd., particle size 63 μm)

[0069] "Silicon carbide (medium-grain thermal conductive filler)": Product name "GC#1200" (manufactured by Pacific Random Co., Ltd., grain size 10 μm)

[0070] "Aluminum oxide (small particle size thermal conductive filler)": Product name "AX1M" (manufactured by Nippon Steel Chemical & Material Co., Ltd., particle size 1 μm)

[0071] (Comparative Examples 1 to 3) Compositions of Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the blending amount (parts by mass) of each component was changed to that shown in Table 1.

[0072] [Preparation of thermally conductive material] Example 1 Using the composition for thermal conductive material of Example 1, a sheet (an example of a thermal conductive material; thickness: 1.5 mm) was produced in the following procedure. First, a first release film (PET film, product name "Purex A50", manufactured by Toyobo Film Solutions Co., Ltd., thickness: 50 μm) was laid on a predetermined mounting table, and a frame-shaped spacer (inner frame size: 120 mm × 130 mm, thickness: 5 mm) was placed on the first release film. Then, a liquid composition for thermal conductive material was poured inside (inside the inner frame) of the frame-shaped spacer to form an application made of the composition for thermal conductive material on the surface of the first release film (application step). Next, the surface of the application was covered with a second release film so that the application in the spacer was sandwiched between the first release film and the second release film (covering step). Then, the applied material sandwiched between the first release film and the second release film (a laminated film formed by laminating a PET film having a thickness of 5 μm and a PET film having a thickness of 50 μm) was hot-pressed in the spacer to harden the applied material, thereby obtaining a highly thermally conductive material made of the hardened material of the applied material (heating and pressing step). The obtained highly thermally conductive material was sandwiched between the first release film and the second release film. The hot pressing conditions were a heating temperature of 100° C. to 110° C., a pressing time of 5 minutes to 10 minutes, and a pressure of 20 MPa to 40 MPa.

[0073] (Comparative Examples 1 to 3) Using the compositions of Comparative Examples 1 to 3, attempts were made to produce sheets in the same manner as in Example 1. The compositions of Comparative Examples 1 and 3 gave the sheets of Comparative Examples 1 and 3, respectively. Note that the composition of Comparative Example 2 had too high a viscosity and could not be molded into a sheet.

[0074] 〔evaluation〕 (processability) For each composition such as Example 1, the processability was evaluated based on whether or not the composition could be molded into a sheet. The results are shown in Table 1. In Table 1, the case where the sheet could be molded is indicated by "◯", and the case where the sheet could not be molded is indicated by "×".

[0075] (hardness) Seven pieces of 50 mm x 100 mm size were cut out from the molded product of Example 1 (a sheet with a thickness of 1.5 mm (excluding the thicknesses of the first release sheet and the second release sheet)), and these seven pieces were stacked together (thickness: 10.5 mm) to prepare a test piece for hardness measurement. In addition, a constant pressure loader for rubber hardness meter (manufactured by Elastron Co., Ltd.) and an Asker C hardness meter were prepared. The indenter of the hardness meter was brought into contact with the test piece, and the value of the hardness meter was read 30 seconds after the full load was applied, and this was recorded as the hardness (Asker C). The results are shown in Table 1.

[0076] (Thermal Conductivity) A test piece (thickness: 7.5 mm) was prepared by stacking five pieces cut into a size of 30 mm x 30 mm from the molded product (sheet with a thickness of 1.5 mm (excluding the thicknesses of the first release sheet and the second release sheet)) of Example 1, etc. A set of such test pieces was prepared. A polyimide sensor was sandwiched between the set of test pieces, and the thermal conductivity (W / m K) was measured by the hot disk method. A hot disk thermal property measuring device (product name "TPS500", manufactured by Hot Disk Corporation) was used for the measurement. The results are shown in Table 1.

[0077] (sticky) From the sheet having a thickness of 1.5 mm (excluding the thicknesses of the first release sheet and the second release sheet) of the molded article in Example 1, etc., a number of strips having a width of 50 mm were cut out and joined together to form a measurement object having a length of 1000 mm and a width of 50 mm. A rolling ball tackiness test was performed on the measurement object in accordance with JIS Z 0237 to measure the rolling distance (cm) of the ball. The results are shown in Table 1. If the rolling distance of the ball was less than 80 cm, it was judged to be "adhesive", and if the rolling distance of the ball was 80 cm or more, it was judged to be "not adhesive". If the rolling distance of the ball was less than 80 cm, when the test piece was placed vertically, the ball placed on the test piece would not fall off and would remain attached to the test piece. On the other hand, if the rolling distance of the ball was 80 cm or more, when the test piece was placed vertically, the ball placed on the test piece would fall off the test piece.

[0078] (peelability) When the first release film (PET film, thickness: 50 μm) attached to the surface of the molded body such as Example 1 was peeled off from the molded body, whether or not the separated matter such as filler separated from the molded body was transferred to the release film side was visually confirmed based on the following evaluation criteria. Note that a release layer made of a silicone release agent was formed on the surface of the PET film used as the first release film. The results are shown in Table 1.

[0079] <Evaluation criteria> If no separated matter or only a very small amount of separated matter is found on the release film, the answer is "○". If any separated material is found on the release film, mark as "X".

[0080] [Table 1]

[0081] (Thermal conductivity) As shown in Table 1, the thermal conductive material of Example 1 was confirmed to have excellent thermal conductivity, with a thermal conductivity of 9.59 W / m·K.

[0082] Comparative Example 1 did not contain aluminum nitride as a large-diameter thermally conductive filler, but contained silicon carbide (particle size: 63 μm) as a large-diameter thermally conductive filler. In such Comparative Example 1, the thermal conductivity was 6.10 W / m·K, and the thermal conductivity was insufficient. In addition, as described below, there was a problem with peelability.

[0083] Comparative Example 2 is a case where the blending amount of the thermally conductive filler is too large (particularly, the blending amount of the large particle diameter thermally conductive filler is too large). In such a case, as described above, the viscosity of the thermally conductive material composition became too high, and it was not possible to form a sheet.

[0084] Comparative Example 3 does not contain aluminum nitride as a large-diameter thermally conductive filler, but contains silicon carbide (particle size: 63 μm) as a large-diameter thermally conductive filler. In the case of Comparative Example 3, although the thermal conductivity is excellent, there is a problem with peelability as described later.

[0085] (About adhesiveness) It was confirmed that the surface of the thermally conductive material in Example 1 was sticky, while that in Comparative Example 1 and Comparative Example 3 was not sticky.

[0086] (About peelability) In Example 1, a trace amount of separated matter (such as thermally conductive filler) was found to adhere to the first release film. For reference, FIG. 3 shows a case where a trace amount of separated matter was found to adhere to the release film. FIG. 3 is a diagram (photograph) showing a case where a trace amount of separated matter was found to adhere to the release film when the release film was peeled off from the thermally conductive material. Within the circular frame shown in FIG. 3, a state is shown in which a trace amount of separated matter consisting of thermally conductive filler or the like separated from the thermally conductive material adheres to the first release film. Note that even if a trace amount of separated matter adheres to the release film when the thermally conductive material is used, contamination by the separated matter can be minimized by quickly removing the release film, for example.

[0087] In the cases of Comparative Examples 1 and 3, adhesion of separated matter was observed on the first release film. For reference, FIG. 4 shows a case where adhesion of separated matter was observed on the release film. FIG. 4 is a diagram (photograph) showing a case where adhesion of separated matter was observed on the release film when the release film was peeled off from the thermally conductive material. Within the circular frame shown in FIG. 4, a state is shown in which granular (lumpy) separated matter consisting of thermally conductive filler and the like separated from the thermally conductive material is attached to the release film. If such granular separated matter adheres to the release film, there is a risk that the separated matter will peel off from the release film and pollute the surrounding environment. [Explanation of symbols]

[0088] 1...thermal conductive material, 2...acrylic resin layer, 3...thermal conductive filler, 31...large particle size thermal conductive filler, 32...medium particle size thermal conductive filler, 33...small particle size thermal conductive filler, 4, 5...release film

Claims

1. an acrylic composition including an acrylic polymer obtained by polymerizing one or more (meth)acrylates, and one or more (meth)acrylates; A multifunctional monomer, A polymerization initiator; A thermally conductive material composition comprising a thermally conductive filler, the blending amount of the polyfunctional monomer is 0.1 parts by mass or more and 0.5 parts by mass or less, the blending amount of the polymerization initiator is 0.1 parts by mass or more and 1.5 parts by mass or less, and the blending amount of the thermally conductive filler is 1550 parts by mass or more and 1600 parts by mass or less, relative to 100 parts by mass of the acrylic composition, The thermally conductive filler includes a large-particle-size thermally conductive filler having a particle size of 50 μm or more and 150 μm or less and made of aluminum nitride, a medium-particle-size thermally conductive filler having a particle size of 7.5 μm or more and 20 μm or less and made of silicon carbide, and a small-particle-size thermally conductive filler having a particle size of 0.5 μm or more and 3 μm or less and made of aluminum oxide, A composition for thermally conductive materials, wherein the amount of the large particle diameter thermally conductive filler blended is 680 parts by mass or more and 750 parts by mass or less per 100 parts by mass of the acrylic composition.

2. 2. The composition for thermally conductive materials according to claim 1, wherein the amount of the medium-sized thermally conductive filler blended is 300 parts by mass or more based on 100 parts by mass of the acrylic composition.

3. 3. The composition for thermal conductive materials according to claim 1, wherein the amount of the small particle diameter thermally conductive filler per 100 parts by mass of the acrylic composition is greater than the amount of the medium particle diameter thermally conductive filler per 100 parts by mass of the acrylic composition.

4. A cured product of the thermal conductive material composition according to any one of claims 1 to 3, A thermally conductive material having a thermal conductivity of 7.2 W / m·K or more and 9.59 W / m·K or less.

5. A method for producing a thermally conductive material by using the composition for thermally conductive material according to any one of claims 1 to 3, comprising the steps of: a step of applying the thermal conductive material composition to a surface of a first release film to form an application comprising the thermal conductive material composition; a covering step of covering a surface of the object with a second release film so that the object is sandwiched between the first release film and the second release film; and a heating and pressurizing step of hot-pressing the additive sandwiched between the first release film and the second release film to harden the additive, thereby obtaining a highly thermally conductive material consisting of the hardened product of the additive.

Citation Information

Patent Citations

  • Sealing material comprising gradient structure in filler concentration, and method for molding the same

    JP1999273934A

  • Production process of nitride ceramic sintered body

    JP2001192272A

  • Composition for forming acrylic thermally conductive composition, thermally conductive sheet and its manufacturing method

    JP2006111644A

  • Nonaqueous electrolyte secondary battery

    JP2016164868A

  • Thermoconductive adhesive sheet, and semiconductor device

    JP2021036022A